2013
DOI: 10.5194/bg-10-2049-2013
|View full text |Cite
|
Sign up to set email alerts
|

Bathymetrical distribution and size structure of cold-water coral populations in the Cap de Creus and Lacaze-Duthiers canyons (northwestern Mediterranean)

Abstract: Abstract. Submarine canyons are known as one of the seafloor morphological features where living cold-water coral (CWC) communities develop in the Mediterranean Sea. We investigated the CWC community of the two westernmost submarine canyons of the Gulf of Lions canyon system: the Cap de Creus Canyon (CCC) and Lacaze-Duthiers Canyon (LDC). Coral associations have been studied through video material recorded by means of a manned submersible and a remotely operated vehicle. Video transects have been conducted and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 77 publications
5
53
1
1
Order By: Relevance
“…The fauna observed associated within the canyons studied here (see also Davies et al, this issue) have also been observed in the neighbouring Whittard Canyon , Morris, 2011and Morris et al, 2013 and other European canyon systems (Cartes et al, 2009 andGori et al, 2013). In general the observed fauna are also known from the wider area incorporating the Rockall Trough and neighbouring banks and seamounts, Porcupine Bank and Seabight (Bullimore et al, 2013, Howell et al, 2010a, Howell et al, 2010b, Narayanaswamy et al, 2013and Tyler and Zibrowius, 1992 and could not be considered to be unique to these canyon features.…”
Section: Canyon and Mini-mound Faunasupporting
confidence: 69%
“…The fauna observed associated within the canyons studied here (see also Davies et al, this issue) have also been observed in the neighbouring Whittard Canyon , Morris, 2011and Morris et al, 2013 and other European canyon systems (Cartes et al, 2009 andGori et al, 2013). In general the observed fauna are also known from the wider area incorporating the Rockall Trough and neighbouring banks and seamounts, Porcupine Bank and Seabight (Bullimore et al, 2013, Howell et al, 2010a, Howell et al, 2010b, Narayanaswamy et al, 2013and Tyler and Zibrowius, 1992 and could not be considered to be unique to these canyon features.…”
Section: Canyon and Mini-mound Faunasupporting
confidence: 69%
“…Similarly, distribution of corals and sponges at the heads of shelf-incising canyons seems to be related to strong currents that expose underlying bedrock in these areas (De Mol et al, 2011). At a smaller scale, steep features of exposed rock, such as vertical walls and overhangs, facilitate the settlement of the scleractinian corals L. pertusa and Madrepora oculata (Freiwald et al, 2009;Huvenne et al, 2011;Gori et al, 2013;Morris et al, 2013;Davies et al, 2014;Fabri et al, 2014).…”
Section: Canyon Effects On Benthic Sessile Fauna and Infaunamentioning
confidence: 99%
“…Sea Orejas et al, 2009;Fink et al, 2013;Gori et al, 2013) demonstrate the potential use of these technologies for future discoveries.…”
Section: Hebbeln Et Al: Environmental Forcing Of the Campeche Colmentioning
confidence: 99%